Sequestering of Fe and Pb ions from Wastewater by Canarium schweinfurthii after carbonization and chemical treatment: Isothermal and Kinetic Modeling - Bassey Uwem; Edjere Oghenekohwiroro; Otolo Solomon Ebiye (Journal of Applied Sciences and Environmental Management)
In this paper agricultural waste; Canarium schweinfurthii was explored for the sequestering of Fe and Pb  ions from wastewater solution after carbonization and chemical treatment at 400oC. Optimum time of 30 and 150 min with percentage removal of 95 and 98% at optimum pH of 2 and 6 was obtained for Fe and Pb ions. Kinetics model followed pseudofirst order as sum of absolute error (EABS) between Qe and Qc greater than that of pseudo second order. Parameters evaluated from isothermal equation (Freundlich and Langmuir) showed that KL and QO for Fe > Pb and R2 for Langmuir> Freundlich. The study reveals the suitability of the adsorbent for sequestering of Fe and Pb ions from industrial wastewater. ©JASEM